Memperkuat identitas nasional di era globalisasi: Tantangan dan strategi - Hikmah, Liwaul (Maliki Interdisciplinary Journal, 2025)
National identity is a fundamental foundation in shaping collective consciousness and strengthening national unity. Amid the waves of globalization that bring new values and foreign cultural influences, national identity faces serious challenges that can erode a nation’s self-identity. Globalization not only impacts the economy and technology but also affects the culture and values that influence a nation’s social systems and ideology. In this context, national identity is no longer static but continuously transforms amidst the encounter of local and global values. This article discusses the urgency of maintaining and strengthening national identity in the rapid and massive era of globalization. This research employs a qualitative method with a literature study approach, reviewing various scientific sources and policies related to national identity, citizenship, and the impact of globalization on culture. The main focus of this study includes the conceptual understanding of national identity, the influence of globalization on national character, and concrete strategies that can be undertaken by the state, educational institutions, media, and the broader society to reinforce national values. The results indicate that character education based on Pancasila, strengthening nationalist narratives in the media, preserving local culture, and synergy among stakeholders are crucial strategic steps to maintain the existence of national identity. Therefore, all elements of the nation need to develop a collective awareness that national identity is the ultimate defense in preserving Indonesia’s unity and sovereignty amidst increasingly complex global competition. Artikel ini membahas urgensi mempertahankan dan memperkuat identitas nasional di tengah era globalisasi yang cepat dan masif. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur, mengkaji berbagai sumber ilmiah dan kebijakan terkait identitas nasional, kewarganegaraan, serta dampak globalisasi terhadap kebudayaan. Fokus utama kajian ini meliputi pemahaman konseptual tentang identitas nasional, pengaruh globalisasi terhadap karakter bangsa, serta strategi konkret yang dapat diambil oleh negara, lembaga pendidikan, media, dan masyarakat luas dalam memperkuat nilai-nilai kebangsaan. Hasil kajian menunjukkan bahwa pendidikan karakter berbasis Pancasila, penguatan narasi kebangsaan di media, pelestarian budaya lokal, serta sinergi antarpemangku kepentingan merupakan langkah strategis yang krusial untuk menjaga eksistensi identitas nasional. Oleh karena itu, seluruh elemen bangsa perlu memiliki kesadaran kolektif bahwa identitas nasional adalah benteng terakhir dalam menjaga keutuhan dan kedaulatan Indonesia di tengah kompetisi global yang semakin kompleks.